2020
DOI: 10.1097/sap.0000000000002371
|View full text |Cite
|
Sign up to set email alerts
|

Different Surgical Reconstructions for Femoral Nerve Injury

Abstract: Background Femoral nerve palsy can cause loss in quadriceps function and knee extension disability, which may lead to severe lower extremity impairment. The obturator nerve trunk transfer in the pelvic, the obturator nerve mortal branches transfer out of the pelvic, along with nerve graft, was introduced years ago to restore femoral nerve function. However, the outcomes of these procedures have never been compared. The aims of this study were to give our experiences in surgical reconstruction for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Four studies (n = 29) report outcomes for patients undergoing sural nerve grafting for isolated femoral nerve injuries. 15,48,50,56 In all cases, preoperative knee extension was absent. In one study, 23 patients were followed after surgery, with 12 recovering MRC grade 3 knee extension.…”
Section: Nerve Graftingmentioning
confidence: 90%
See 2 more Smart Citations
“…Four studies (n = 29) report outcomes for patients undergoing sural nerve grafting for isolated femoral nerve injuries. 15,48,50,56 In all cases, preoperative knee extension was absent. In one study, 23 patients were followed after surgery, with 12 recovering MRC grade 3 knee extension.…”
Section: Nerve Graftingmentioning
confidence: 90%
“…50 Six patients from the other three studies had more detailed preoperative and follow-up information. 15,48,56 For these patients, the mean preoperative interval was 3.3 + 1.2 months. The mean graft length (n = 6) used during surgery was 7.0 + 4.4 centimeters (cm).…”
Section: Nerve Graftingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nerve grafts can either entail an end-to-end nerve suture or suturing an autologous donor nerve to replace the damaged portion of the recipient nerve [ 108 , 109 ]. Various case reports highlight the effectiveness of this strategy, namely restoring the functionality of the femoral, obturator, and sciatic nerves, as well as for multilevel injuries involving nerve roots [ 102 , 103 , 107 , 110 , 111 ]. Across these various procedures, it was reported that related motor and sensory function was successfully restored, including hip adduction, hip flexion, and knee extension [ 102 , 103 , 107 , 110 , 111 ].…”
Section: Treatment and Managementmentioning
confidence: 99%
“…11,12 Mild sensory deficits have been found in patients obturator transfer to the femoral nerve, but patients did not find this sensory loss to be limiting. 40 Deficits after branches of the tibial nerve are used as donor nerves include deficits in toe flexion, decreased calf circumference, or decreased ankle plantarflexion. 25 However, these deficits must be weighed against the potential benefits of a successful nerve transfer.…”
Section: Complicationsmentioning
confidence: 99%